Integration of Web-Based Intelligent Tutoring System (TuinLec) into Text Structure Strategy to Improve Text Strategy Memory and Reading Comprehension Skills - Kusumawati, Endah Tri; Solihati, Nani; Sari, Zamah (International Journal of Learning, Teaching and Educational Research, 2025)
Text strategy memory is an essential element in students’ reading comprehension level, so the function of this element must be optimized through the right strategy. This study aimed to investigate the impact of a web-based intelligent tutoring system (TuinLec) integrated with text structure strategy on text strategy memory and reading comprehension skills. TuinLec emphasizes procedural strategies or approaches that emphasize content so that various discussion variations are created. This study used a quasi-experimental method involving 300 elementary school students who focused on grades four and five because they were transitioning to understand more complex texts. Multinomial logistic regression data analysis with Statistical Analysis System to investigate whether students in the intervention group showed an increase in organized memory structures better than students in the control group. The results showed that integrating a web-based intelligent tutoring system (TuinLec) in a text structure strategy proved effective in improving text strategy memory and reading comprehension skills. The improvement of memory structure is seen in the organization of the written reading memory structure from the beginning, which was random, and only a list of memories was written to be well organized. In addition, the improvement of reading comprehension skills and text strategy memory skills is also seen in several competencies, namely the problem and solution memory structure, the ability to analyze the issues and solutions, the memory structure of comparison, the ability to analyze comparisons, the main idea memory structure, and the ability to identify main ideas. This study implies that text structure can be used as an alternative strategy for understanding text comprehensively. Through this study, text structure can become a strategy by integrating it with technology to facilitate students in gaining a comprehensive understanding.